Capital structure determinants of private small and medium-sized enterprises in China - Newman, Alexander (2010)
This thesis examines the capital structure determinants of private SMEs in China and the extent to which financial theories of capital structure adequately explain their financing behaviour. It also investigates whether other theoretical perspectives can be utilised to explain their capital structure decisions.